Differentiation of Pyogenic Brain Abscesses from Necrotic Glioblastomas with Use of Susceptibility-Weighted Imaging - Toh, C.H.; Wei, K.-C.; Chang, C.-N.; Hsu, P.-W.; Wong, H.-F.; Ng, S.-H.; Castillo, M.; Lin, C.-P. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: A common imaging finding in brain abscess and necrotic glioblastoma is a T2 hypointense margin. The features of this hypointense rim on SWI have not been previously described, to our knowledge. We aimed to differentiate abscesses from glioblastomas by assessing the morphology of their lesion margin by using SWI. MATERIALS AND METHODS: T2WI and SWI were performed in 12 abscesses and 20 rim-enhancing glioblastomas. On T2WI and SWI, the prevalence and the border types (complete versus incomplete) of hypointense rims were qualitatively assessed. On SWI, the contour (smooth versus irregular) and the location of hypointense rims relative to the contrast-enhancing rims as well as the prevalence of the “dual rim sign,” defined as 2 concentric rims at lesion margins with the outer one being hypointense and the inner one hyperintense relative to cavity contents, were also analyzed. RESULTS: Prevalence and the border types of the hypointense rims on T2WI were not different between abscesses and glioblastomas. On SWI, there were significantly more hypointense rims that were complete (P < .001) and smooth (P < .001), having the same location as the contrast-enhancing rims (P < .001) for abscesses. A dual rim sign was present in 9 of 12 abscesses but absent in all glioblastomas (P < .001). CONCLUSIONS: SWI may be helpful in differentiating pyogenic abscesses from necrotic glioblastomas. The dual rim sign is the most specific imaging feature distinguishing the 2. GRAPPAgeneralized autocalibrating partially parallel acquisitionmIPminimum intensity projectionMPRAGEmagnetization-prepared rapid acquisition of gradient echoSWIsusceptibility-weighted imaging